If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 = 15y + -3y Combine like terms: 15y + -3y = 12y 72 = 12y Solving 72 = 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 72 + -12y = 12y + -12y Combine like terms: 12y + -12y = 0 72 + -12y = 0 Add '-72' to each side of the equation. 72 + -72 + -12y = 0 + -72 Combine like terms: 72 + -72 = 0 0 + -12y = 0 + -72 -12y = 0 + -72 Combine like terms: 0 + -72 = -72 -12y = -72 Divide each side by '-12'. y = 6 Simplifying y = 6
| 54x=-9 | | 33s^2=15 | | -2/5z=4/15 | | 8(x-3)=06 | | 82l^7=136 | | 5/9x=5/81 | | 5+4.2=-8.3 | | 2a^1=36 | | u^3*10=70 | | N+37=85 | | q^8*6=18 | | (5(3)(-1^3)/4(2^2))^2 | | e^4*3=15 | | N-65=188 | | 48=3+9x | | 2x+x+5=70*2 | | 16/36=z/54 | | 1/3x-1/5=-1/2 | | 2x+x+5=70 | | (2y-2)+2(y-3)=25 | | [x-1]+2= | | (x-2)+2(y-3)=22y | | -8+2=18 | | 2x^2=(x+2)(x-3)+12 | | (x-2)+2(y-3)=25 | | 1/x-1/y=7/2 | | 6x+27=13x-37 | | 18w=19 | | 15y=14(y+17) | | r+13=19 | | 20d=17 | | n+-1=6 |